Severity and prevalence of burnout syndrome in paediatric intensive care nurses: A systematic review. (December 2021) - Matsuishi, Yujiro; Mathis, Bryan J.; Masuzawa, Yuko; Okubo, Nobuko; Shimojo, Nobutake; Hoshino, Haruhiko; Enomoto, Yuki; Inoue, Yoshiaki
Abstract: Objectives: The aim of this study is to identify burnout syndrome severity and prevalence in paediatric intensive care unit nurses. Design: Systematic review. Setting: Paediatric intensive care unit. Main outcome measures: A librarian was consulted on methodology before the search process. MEDLINE (via PubMed), EMBASE, the Cochrane Library, CINAHL, and PsycINFO were searched for full-text studies published before September 2019 in any language. Only those observational studies exploring burnout syndrome, including paediatric intensive care unit nurses, were included. Two authors independently screened studies. We assessed the risk of bias within each study based on the Office of Health Assessment and Translation tool. Result: After screening 1238 articles, we identified six studies which met the systematic review criteria. All studies included were published after 2012 and participant sample sizes were between 35 and 195 nurses. Three studies were conducted in the United States of America while the others were from the United Kingdom, Turkey and Taiwan. Prevalence of burnout syndrome in pediatric intensive care unit nurses was reported in these studies as between 42% and 77%. The assessment tools used in these studies were the (abbreviated) Maslach Burnout Inventory, Abbreviated Maslach Burnout Inventory, Occupational Burnout Inventory, and Professional Quality of Life Scale Version 5. We could not conduct a meta-analysis due to the lack of studies. Conclusion: Our systematic review identifies that a low number (6 total) of relevant studies focused on burnout syndrome for pediatric intensive care unit nurses with a prevalence of burnout syndrome in paediatric intensive care unit nurses of between 42% and 77%.